Experiences And Challenges Of Community Participation In Urban Renewal Projects: The Case Of Johannesburg, South Africa - Thwala, Wellington Didibhuku (Penerbit Universiti Sains Malaysia, 2009)
Urban renewal and inner city regeneration have become critical efforts for the South African government, which has invested in several structures to stem the tide of decline in its nine major cities. Commitment to the alleviation of poverty is a focal point of the renewal and regeneration agenda and will remain so in the future. This effort is motivated by the fact that around 24% of the South African population currently lives on less than USD 1.00 per day, below the poverty line defined by the World Bank. The Central Government has made numerous public commitments to development, a part of which concerns extensive infrastructure investment and service delivery. Communities are expected to participate fully in the planning and implementation of these urban renewal projects. To this aim, participation is a process through which stakeholders influence and share control over development initiatives and the decisions and resources which affect them. Community participation should be aimed at empowering people by ensuring the development of skills and the creation of employment opportunities. This paper first explores the concept of community participation, and will then look at relevant past experiences in relation to community participation in urban renewal projects. Furthermore, the paper outlines the challenges and problems of community participation in urban renewal projects in Johannesburg, and finally, close with recommendations for the future